2010
DOI: 10.1111/j.1863-2378.2009.01267.x
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter spp. in Broiler Flocks at Farm Level and the Potential for Cross‐Contamination During Slaughter

Abstract: Screening of broiler flocks for their Campylobacter carriage on farm level and consequently the spread of Campylobacter spp. during slaughtering can help to identify hygiene control points. Therefore, between December 2001 and August 2002 in total 51 broiler flocks from three farms of different geographical regions in Germany were analysed for thermophilic Campylobacter. Campylobacter spp. were isolated from 45% of the broiler flocks examined. Subsequently, 1101 samples were taken from 22 flocks during differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
4
33
1
1
Order By: Relevance
“…The Campylobacter-infected flocks may be a source of these bacteria for the corresponding carcasses, although the presence of the same bacterial species in the paired samples (flock -carcass) might also be due to cross-contamination during a slaughter process. These kind of transmission was also confirmed by other authors (Allen et al 2007, Ellerbroek et al 2010. Furthermore, the identification of other Campylobacter species on carcasses than those in the original flocks may also suggest a different contamination sources and routes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The Campylobacter-infected flocks may be a source of these bacteria for the corresponding carcasses, although the presence of the same bacterial species in the paired samples (flock -carcass) might also be due to cross-contamination during a slaughter process. These kind of transmission was also confirmed by other authors (Allen et al 2007, Ellerbroek et al 2010. Furthermore, the identification of other Campylobacter species on carcasses than those in the original flocks may also suggest a different contamination sources and routes.…”
Section: Discussionsupporting
confidence: 72%
“…These findings should be further tested using methods for molecular characterization of the Campylobacter isolates of the same species (Normand et al 2008). During processing, the spread of Campylobacter and the cross-contamination of broiler carcasses by the bacteria present in the intestinal content may create a hygiene problem (Ellerbroek et al 2010). The results of the present and other studies suggest that control mechanisms at slaughterhouses may be more promising than countermeasures being applied at the farm level only; however, the complete elimination of Campylobacter during processing is probably not possible (Allen et al 2007, Reich et al 2008.…”
Section: Discussioncontrasting
confidence: 39%
“…This study also indicated that bovine fecal Campylobacter strains can colonize chickens, which was confirmed later on by Patriarchi et al (2011). On a German farm, indistinguishable isolates of clonal origin were found in different flocks during the same rearing period (Ellerbroek et al 2010). This suggests that Campylobacter strains might be transmitted from one broiler flock to another or might point toward a common external source infecting multiple broiler flocks at the same farm.…”
Section: Sources For Horizontal Campylobacter Transmission To Broilersupporting
confidence: 61%
“…Also, the time of year clearly has an influence. In Germany and the United Kingom, the risk for broilers to become colonized with Campylobacter is highest during the summer months (McDowell et al 2008, EllisIversen et al 2009, Ellerbroek et al 2010, Jorgensen et al 2011) and a coincident seasonality of infections in chickens and humans has been shown (Meldrum et al 2005). In the EUwide baseline survey on Campylobacter in broiler batches in 2008, batches were most likely to be found Campylobacter colonized in the third quarter ( July-September) of the year (EFSA 2010b).…”
Section: Initial Broiler Flock Colonization and Colonization Patternmentioning
confidence: 99%
See 1 more Smart Citation